Federalism, Freedom of Movement, and Fiscal Equalization - Stefan Traub (Kiel University, Department of Economics, 2003)
In this paper, we take up the question why a group of sovereign countries is willing to form a federation even if residents of the high-income region suspect potential immigrants to be net beneficiaries of the tax and transfer system. We argue that income uncertainty alone cannot satisfactorily explain the formation of federations, since in many existing and developing federations income differences are both large and persistent. In the model presented here remaining separated involves costs for the high-income region, which can be regarded as a proxy for the efficiency loss caused if mobile factors cannot reallocate. A fiscal equalization scheme that shares the resources saved by limiting costly migration between the regions can make both regions better off.
urn:nbn:de:101:1-200911021986
Keywords: D63; H40; H77; D78; 330; Federalism; Migration; Fiscal Equalization; Föderalismus; Finanzausgleich; Finanzföderalismus; Regionale Einkommensverteilung; Internationale Wanderung; Internationale Faktormobilität; Allokationseffizienz; Kosten-Nutzen-Analyse; Wohlfahrtseffekt; Theorie